2023
DOI: 10.1021/jacs.2c09837
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the Reactive Uptake of Chlorine Nitrate at the Air–Water Interface

Abstract: It is well-known that the aqueous-phase processing of chlorine nitrate (ClONO 2 ) plays a crucial role in ozone depletion. However, many of the physical and chemical properties of ClONO 2 at the air−water interface or in bulk water are unknown or not understood on a microscopic scale. Here, the solvation and hydrolysis of ClONO 2 at the air−water interface and in bulk water at 300 K were investigated by classical and ab initio molecular dynamics (AIMD) simulations combined with free energy methods. Our results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
0
11
0
1
Order By: Relevance
“…The solvation and adsorption of these two molecules have been calculated previously. It was observed that ClONO 2 and HOCl have lower free energy at the air–water interface than in the gas phase and bulk liquid water, indicating that these two molecules have an affinity for the air–water interface. , Here, AIMD simulations coupled with the metadynamics method were performed to calculate the free-energy change as a function of the distance between ClONO 2 and HOCl at the air–water interface and in bulk liquid water, as shown in Figure a. The minima of the free-energy profiles for the molecules at the air–water interface and for the molecules in the bulk liquid water are located at d = 5.12 and 5.06 Å, respectively, reflecting that ClONO 2 and HOCl prefer to form complexes both at the air–water interface and in the bulk liquid water.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The solvation and adsorption of these two molecules have been calculated previously. It was observed that ClONO 2 and HOCl have lower free energy at the air–water interface than in the gas phase and bulk liquid water, indicating that these two molecules have an affinity for the air–water interface. , Here, AIMD simulations coupled with the metadynamics method were performed to calculate the free-energy change as a function of the distance between ClONO 2 and HOCl at the air–water interface and in bulk liquid water, as shown in Figure a. The minima of the free-energy profiles for the molecules at the air–water interface and for the molecules in the bulk liquid water are located at d = 5.12 and 5.06 Å, respectively, reflecting that ClONO 2 and HOCl prefer to form complexes both at the air–water interface and in the bulk liquid water.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in a comparison of the computed free-energy surface for gas-phase and air–water interface systems, the air–water interface can markedly lower the free-energy barrier to hypochlorous acid (HOCl) and nitric acid (HONO 2 ) formation through the reaction of ClONO 2 with water (reaction ). ClONO 2 + normalH 2 normalO HOCl + HONO 2 In an experimental study of the heterogeneous reactions of ClONO 2 on ice, Tolbert et al discovered the presence of dichlorine monoxide (Cl 2 O). The Cl 2 O concentration was reported to increase upon ClONO 2 exposure to ice.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(e) In situ liquid/liquid interfacial transfer kinetics by the single nanodroplet electrochemistry [33] 增进通过SFG光谱在界面氨基酸分子微观结构上的差 异化认识. 而针对ClONO 2 在空气-水界面的微观反应吸 附机制研究方面, Wan等人 [19] 采用经典和从头算分子 动力学(ab initio molecular dynamics, AIMD)模拟, 并 结合自由能方法, 确认了ClONO 2 更易于在界面处富集, 其中Cl [57] 和成核生长动力 学 [58] . 微液滴化学已经成为当前热门的研究领域.…”
unclassified